البلاغة منهجا وتعليما وتعلما من وجهة نظر طلاب كلية اللغات والإدارة - Eltingari, Salih Mahgoub Mohamed; Hassan, Fekri Abidin; Abdul Rahman Ibrahim, Muhammad (2021)
This research studies the subject of rhetoric, from curriculum, teaching and learning aspects, at the Faculty of Languages and Management of the International Islamic University Malaysia, through the analytical descriptive method, a questionnaire was designed and then distributed to a sample of 33 students. After analysis, the following results were obtained: The sample finds it difficult to move directly from reality to metaphor, this is because the curriculum does not contain Arabic literature, members of the sample are not aware of the existence of rhetorical chapters for them to study, and it is not existent in the Holy Quran, and the prophetic traditions, the need to rely on the Holy Quran and Hadith when drawing rhetorical examples, and to stay as much as possible from poetry, members of the sample does not like to participate in the classroom. The research has recommended the need to link the metonymy and allegory in the student’s mother tongue with Arabic language.